The future workplace depends on efficiency, effectiveness, and balance : in order to shift from survival mode to growth mode, companies need to embrace thoughtful work design - Hooijberg, Robert; Watkins, Michael (MIT Sloan Management Review, 2022)
As leaders focus on growing their businesses as the world emerges from the pandemic, they must keep efficiency, effectiveness, and quality of life in balance. The authors explain why the future workplace depends on leaders’ ability to maintain that balance while designing hybrid work thoughtfully, investing in organizational culture, and providing the resources that will enable their teams to do their best work.